The willingness to pay for job amenities : evidence from mothers' return to work - Christina Felfe (Center for Economic Studies and ifo Institute (CESifo), 2009)
This study is the first to estimate mother's marginal willingness to pay (MWP) for job amenities directly. Its identification strategy relies on German maternity leave length. The key aspect of the maternal leave framework is that mothers can decide whether and when to return to their guaranteed job. Thus, in contrast to previous studies that analyze the job search of employed workers, this framework allows us to overcome the limitation of not observing the wage/amenity offer process. A theoretical model of the leave length decision is derived from a random utility approach. Using data from the German Socio-Economic Panel and the Qualification and Career Survey, this model is estimated by a discrete duration method. The MWP for amenities can be inferred through the estimated elasticities of the leave length with respect to the amenities and the wage. The results provide evidence that mothers are willing to sacrifice a significant fraction of their wage to reduce hazards (22%) and to enjoy a flexible working schedule (36-56%).
Keywords: J31; J33; J22; 330; marginal willingness to pay; maternal labor supply; discrete duration models; Mütter; Frauenerwerbstätigkeit; Arbeitsangebot; Berufliche Integration; Willingness to pay; Arbeitszeitflexibilisierung; Betriebliche Sozialleistungen; Theorie; Deutschland